1999
DOI: 10.1046/j.1440-1711.1999.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Does HIV cause depletion of CD4+ T cells in vivo by the induction of apoptosis?

Abstract: SummaryThe central pathogenic feature of AIDS is the dramatic loss of CD4+ lymphocytes. Despite more than a decade of intense research, the exact mechanism by which HIV causes this is still not understood. A major model for T cell depletion, proposed originally by Ameison and Capron in a report published in 1991, is that HIV sensitizes CD4+ T cells for activation-induced apoptosis. The apoptotic model of T cell depletion is discussed, and experiments that address the questions of whether apoptosis is restricte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2001
2001
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 102 publications
0
20
0
2
Order By: Relevance
“…However, the large amount of evidence demonstrating that CD4 regulates apoptosis has been obtained after separate ligation of CD4 and TCR (11, 40 -43). This has been a good approach to analyze the effects of CD4 antagonist ligands such as anti-CD4 Abs (44) or HIV gp120 (45,46). Indeed, this approach has provided useful information to control autoimmune diseases and organ graft rejection and to explain CD4 ϩ T cell deletion in AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the large amount of evidence demonstrating that CD4 regulates apoptosis has been obtained after separate ligation of CD4 and TCR (11, 40 -43). This has been a good approach to analyze the effects of CD4 antagonist ligands such as anti-CD4 Abs (44) or HIV gp120 (45,46). Indeed, this approach has provided useful information to control autoimmune diseases and organ graft rejection and to explain CD4 ϩ T cell deletion in AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has been implicated in the cytopathicity of several human and animal viruses, including retroviruses such as HIV-1 (7,9,26). Apoptosis is defined as an active physiological process of cellular self-destruction, distinguished by a specific series of morphological and biochemical changes that stem from the activation of the caspase family of cysteine proteases (45).…”
Section: Aids Pathogenesis Is Characterized By a Major Decline In Cirmentioning
confidence: 99%
“…Evidence has suggested that apoptosis could play a role in both direct killing of infected CD4 ϩ T cells, as well as in the death of uninfected bystander CD4 ϩ T cells (26). The first reports documenting HIV-1-induced apoptosis demonstrated fragmentation of cellular DNA among infected T-cell cultures (32,55).…”
Section: Aids Pathogenesis Is Characterized By a Major Decline In Cirmentioning
confidence: 99%
“…These include the direct lysis of CD4 ϩ T cells from virus infection (26), syncytium formation (44,77), superantigen-mediated deletion (34,66), macrophage-dependent killing (8), and CD8 ϩ T-cell-dependent killing (76). Apoptosis has also been implicated as a mechanism for the death of both HIV-infected and uninfected cells (30,35). However, differences between experimental systems and the direct cytopathic effects of replicating virus have complicated interpretation of these studies, and it is still largely unresolved as to whether noninfectious HIV virions can induce apoptosis and cell death.…”
Section: Infection Of Humans With Human Immunodeficiency Virus (Hiv) mentioning
confidence: 99%